Impact of counselling on exclusive breast-feeding practices in a poor urban setting in Kenya: a randomized controlled trial - Ochola, Sophie A; Labadarios, Demetre; Nduati, Ruth W (Public health nutrition, 2013)
To determine the impact of facility-based semi-intensive and home-based intensive counselling in improving exclusive breast-feeding (EBF) in a low-resource urban setting in Kenya. A cluster randomized controlled trial in which nine villages were assigned on a 1:1:1 ratio, by computer, to two intervention groups and a control group. The home-based intensive counselling group (HBICG) received seven counselling sessions at home by trained peers, one prenatally and six postnatally. The facility-based semi-intensive counselling group (FBSICG) received only one counselling session prenatally. The control group (CG) received no counselling from the research team. Information on infant feeding practices was collected monthly for 6 months after delivery. The data-gathering team was blinded to the intervention allocation. The outcome was EBF prevalence at 6 months. Kibera slum, Nairobi. A total of 360 HIV-negative women, 34-36 weeks pregnant, were selected from an antenatal clinic in Kibera; 120 per study group. Of the 360 women enrolled, 265 completed the study and were included in the analysis (CG n 89; FBSICG n 87; HBICG n 89). Analysis was by intention to treat. The prevalence of EBF at 6 months was 23.6% in HBICG, 9.2% in FBSICG and 5.6% in CG. HBICG mothers had four times increased likelihood to practise EBF compared with those in the CG (adjusted relative risk = 4.01; 95% CI 2.30, 7.01; P=0.001). There was no significant difference between EBF rates in FBSICG and CG. EBF can be promoted in low socio-economic conditions using home-based intensive counselling. One session of facility-based counselling is not sufficient to sustain EBF.